Effect of doping on the performance of multiple quantum well infrared photodetector. Issue 5 (10th May 2018) - Billaha, Md. Aref; Das, Mukul K.; Kumar, Subindu
Abstract : This study theoretically analyses the performance of multiple quantum well infrared photodetector mainly with the variation of active layer doping. However, the effect of temperature and applied bias has also been studied. Results show that the effect of doping on the responsivity is significant whereas on the dark current is less significant. Effect of temperature on the dark current is more significant compared with that of doping concentration. Moreover, concerning the detectivity of the device, choice of doping plays a significant role on the detector.